Effect of moderate exercise under hypoxia on Th1/Th2 cytokine balance - Santos, Samile A.; Lira, Fabio S. [UNESP]; Silva, Edgar T.; Caris, Aline; Oyama, Lila M.; Thomatieli-Santos, Ronaldo (Wiley-Blackwell, 2019)
Introduction and objective Moderate exercise performed in normoxia can be immunostimulatory, while strenuous exercise can be immunosuppressive. However, less is known about the effects of exercise under hypoxia on cytokines. The aim of this study was to evaluate the effects of an acute exercise session performed under hypoxia similar to an altitude of 4200 m on cytokine balance. Our hypothesis was that exercise, even of moderate intensity, associated with hypoxia may induce different changes in relation to the normoxic condition. Methods Eight healthy male volunteers were exercised on a treadmill for 1 hour at an intensity of 50% VO2peak under normoxic or hypoxic condition (4200 m). Blood samples were collected at rest and immediately 1 hour after the exercise, respectively to determine cytokines, hormones and metabolites. The two-way ANOVA and the Bonferroni post hoc test were used and the significance adopted was P While IL-2, the IL-2/IL-4 ratio and glutamine decreased under hypoxia, IL-6 and IL-1ra increased. There were increases in the IL-2/IL-4 ratio, IL-6, IL-1ra and IL-10/TNF-alpha in normoxia. There were no differences in cortisol or glucose. Conclusion Moderate exercise under hypoxia condition changes the Th1/Th2 balance including IL-2, IL-4 and TNF-alpha cytokines, suggesting a Th2 response after 1 hour rest.
Keywords: cytokines; glutamine; high altitude; inflammation; moderate exercise